2017
DOI: 10.1007/s11205-017-1631-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in Infant Mortality in Egypt: Analyzing Trends Between 1995 and 2014

Abstract: Copyright to papers in this working paper series rests with the authors and their assignees. Papers may be downloaded for personal use. Downloading of papers for any other activity may not be done without the written consent of the authors. Short excerpts of these working papers may be quoted without explicit permission provided that full credit is given to the source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Like in other regions, the infant mortality rate found in the study showed a reduction between the analyzed periods. Although the coefficient of infant mortality has decreased in many regions, inequalities persist (34,40) . In Egypt, the analysis of socioeconomic inequalities in infant mortality showed an inverse association between infant mortality rates and standard measures of life, and the poor have the highest preterm infant mortality (40) .…”
Section: Discussionmentioning
confidence: 99%
“…Like in other regions, the infant mortality rate found in the study showed a reduction between the analyzed periods. Although the coefficient of infant mortality has decreased in many regions, inequalities persist (34,40) . In Egypt, the analysis of socioeconomic inequalities in infant mortality showed an inverse association between infant mortality rates and standard measures of life, and the poor have the highest preterm infant mortality (40) .…”
Section: Discussionmentioning
confidence: 99%
“…Preston (23) puts forward that in higher income regions, the increase of population investment in health can help local people improve their health level. Poor regions struggle to improve health care because of lack of funds (31,32).…”
Section: Hypothesesmentioning
confidence: 99%
“…The GDP in eastern region is generally high and the economy is relatively developed; the GDP in middle region is generally medium and the economy is relatively developing; the GDP in western region is generally low and the economy is relatively backward. Scholars have empirically demonstrated that increased medical resources can significantly reduce local mortality (20,23,25,(31)(32)(33). There are still significant problems of uncoordinated regional development in China.…”
Section: Hypothesesmentioning
confidence: 99%
“…They found substantial inequality of opportunities in early childhood and geographical differences was a key contributor to these inequalities. In another study, Sharaf and Rashad [ 21 ] suggested that while Egypt has managed to improve child health, socioeconomic disparities remain substantial. Additionally, they found that the rapid growth in GDP per capita did not result in lower malnutrition rates in Egypt [ 19 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 2012 and 2013 Jordan and Yemen Demographic and Health Surveys show that the under-five years stunting rate is 7.7 % in Jordan and 46.5 % in Yemen, the second highest rate in the world. Studies reveal that there are significant disparities in child health outcomes between urban and rural regions in the three countries [ 12 , 21 ].…”
Section: Introductionmentioning
confidence: 99%